Parents with neurodevelopmental disorders and their children - Marriott, E (2018)
Adults with neurodevelopmental disorders, such as Attention-Deficit Hyperactivity Disorder (ADHD) or Autism Spectrum Disorder (ASD) face a varying degree of associated challenges and impairment. However, there is a scarcity of literature regarding those adults who go on to become parents. Understanding the experiences of parents with neurodevelopmental disorders and their children is vital in providing the appropriate, specialist support. The first paper systematically reviewed the literature relating to parental ADHD and child externalising, internalising, social and cognitive outcomes. Despite the well-established link between parental ADHD and child ADHD, little is known about other important child outcomes. Twenty-one eligible studies were identified, synthesised and critiqued. The review found that parental ADHD was associated with child externalising problems. However, this was not found for child oppositional defiance disorder. Parenting and parental gender were highlighted as important moderating and mediating factors. Due to low study numbers and quality issues, results were inconclusive regarding child internalising, social and cognitive outcomes. The review highlighted the importance of future research, theory and services addressing the needs of both parents with ADHD and their children. The second paper sought to explore the parenting experiences of adults with ASD who have children with ASD. Little is known about these parents, despite the challenges known to be associated with adult ASD and with parenting a child with ASD. Eight parents were interviewed, and data was analysed using Interpretative Phenomenological Analysis, revealing four superordinate themes. These captured parents’ experiences of the parent-child relationship, the personal impact of parenting, the acceptance and challenge of living with a child with ASD and managing the complexities of professional services. These findings highlighted the need to provide integrated services which address the multiple needs of families with ASD. Future research and theoretical implications were also considered.